Cohesive Markers Found in Thesis Abstracts - Muhassin, Mohammad (Universitas Islam Negeri Raden Intan Lampung, 2018)
The research aims to describe and analyze the lexically and grammatically cohesivemarkers found in students’ thesis abstracts. This is a kind of descriptive-qualitativeresearch. The population of the research consisted of all sentences found in nineabstracts. Meanwhile, the sample included all sentences containing the cohesive markers taken by using purposive sampling technique. The result of the research shows that the lexically cohesive markers found in the data of lexical cohesion are: synonym (18%),repetition (54%), superordinate (12%), and collocation (16%). In addition, the grammatically cohesive markers found in the data of grammatical cohesion are: reference (15%), conjunction (39%), substitution (21%) and ellipsis (25%).